2019
DOI: 10.1021/acs.macromol.9b00145
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hydrogen Bonding Formation and Breaking in Semiconducting Polymers under Mechanical Strain

Abstract: Diketopyrrolopyrrole (DPP) based donor-acceptor conjugated polymers, with increasing amount of weak H-bonding units, namely 2,6-pyridine dicarboxamide (PDCA), inserted as end groups in alkyl sidechains were prepared and investigated. In contrast to previously reported DPP polymers containing PDCA units as conjugation breakers along the polymer backbone, PDCA in the alkyl sidechains readily produced almost quantitative formation of intermolecular H-bonding even at low PDCA unit content (< 10 mol%) as shown by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…DSC measurements for PDPP‐T3 and PNDI‐C0, which have highly planar and rigid backbone structures, are presented in Figure (d,e), the step change in c p , thus the glass transition, cannot be readily seen from the DSC scans. A linear curve is observed and is expected based on various previous reports . PDPP‐T3 shows a small curvature at the vicinity of 0 °C.…”
Section: Resultssupporting
confidence: 86%
“…DSC measurements for PDPP‐T3 and PNDI‐C0, which have highly planar and rigid backbone structures, are presented in Figure (d,e), the step change in c p , thus the glass transition, cannot be readily seen from the DSC scans. A linear curve is observed and is expected based on various previous reports . PDPP‐T3 shows a small curvature at the vicinity of 0 °C.…”
Section: Resultssupporting
confidence: 86%
“…Hydrogen bonding (H bonding) has been widely used to tune intermolecular interactions and self‐assembly structures by considering its relative bonding strength and directionality . On the basis of this consideration, as shown in Scheme and Figure , some of us incorporated urea groups in the side chains of DPP‐based polymers P175–P177 .…”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
“…The semiconducting performances of the damaged devices can be almost fully recovered after a solvent and thermal healing treatment. Recently, they incorporated PDCA units into the side chains of P197–P200 . On the basis of FTIR studies, they concluded that the PDCA units in the side chains as in P197–P200 , are more favorable for the formation of H bonding compared with those in P194–P196 , in which the PDCA units are positioned in the backbones.…”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
“…All synthesized polymers exhibited vibronic shoulders at around 600 nm, representing the existence of molecular ordering and aggregation of the SCPs in the film state. 36 Furthermore, P20 and P30, the random copolymers, exhibited distinct vibronic shoulders of similar intensity in comparison with the homopolymer P0, indicating that the former can form a highly ordered structure despite random copolymerization. However, the intensity of the vibronic shoulder of P10 was lower than that of the other polymers, suggesting not only that the interchain interaction between the polymers of P10 is weaker than in the others, but also that adding a small quantity of different monomer would disrupt the ordering of the polymer chains.…”
Section: Resultsmentioning
confidence: 89%